2004
DOI: 10.1158/1078-0432.ccr-04-0497
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Responsiveness of Glioblastoma Multiforme to Chemotherapy after Vaccination

Abstract: Purpose: Although the development of immune-based therapies for various cancers including malignant glioma has been heralded with much hope and optimism, objective clinical improvements in most vaccinated cancer patients have not been realized. To broaden the search for vaccineinduced benefits, we examined synergy of vaccines with conventional chemotherapy.Experimental Design: Survival and progression times were analyzed retrospectively in 25 vaccinated (13 with and 12 without subsequent chemotherapy) and 13 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
159
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(172 citation statements)
references
References 37 publications
(31 reference statements)
13
159
0
Order By: Relevance
“…In addition, Wheeler et al 13 analyzed survival and the time to disease progression in vaccinated (tumorpulsed DCs) and nonvaccinated patients with glioblastoma who received chemotherapy. Vaccinated patients who received subsequent chemotherapy exhibited significantly longer times to tumor recurrence after chemotherapy relative to their own previous recurrence times and had significantly longer postchemotherapy recurrence times and survival relative to patients who received vaccination or chemotherapy alone.…”
Section: Therapeutic Vaccines Combined With Chemotherapymentioning
confidence: 99%
“…In addition, Wheeler et al 13 analyzed survival and the time to disease progression in vaccinated (tumorpulsed DCs) and nonvaccinated patients with glioblastoma who received chemotherapy. Vaccinated patients who received subsequent chemotherapy exhibited significantly longer times to tumor recurrence after chemotherapy relative to their own previous recurrence times and had significantly longer postchemotherapy recurrence times and survival relative to patients who received vaccination or chemotherapy alone.…”
Section: Therapeutic Vaccines Combined With Chemotherapymentioning
confidence: 99%
“…Unfortunately, this has largely not been realized in patients with glioblastoma multiforme (5). Despite a negligible incidence of metastasis, aggressive surgery, and the application of novel chemotherapeutics, patients with glioblastoma multiforme, the most common and lethal form of primary brain cancer, typically live <1 year from the time of diagnosis (6). Recurrence of tumor following surgical resection and chemotherapy is very high (>90%), and survival of these patients is usually <12 weeks (7).…”
mentioning
confidence: 99%
“…In addition, severely reduced total CD4 + counts (15) and diminished delayed type hypersensitivity (16,17) responses are hallmarks of patients with glioblastoma multiforme. Although the exact nature of T-cell lymphopenia in glioblastoma multiforme is not well understood, recent reports have suggested that mechanisms contributing to this deficiency may include dysregulation of thymic output (6), increased regulatory T-cell (T reg ) fraction (15), and tumor-induced immunosuppression (8). Severe T-cell lymphopenia, especially in the CD4 + compartment, is commonly observed in patients with glioblastoma multiforme (15).…”
mentioning
confidence: 99%
“…But a study conducted in 2004 (Wheeler et al, 2004) showed that vaccination or chemotherapy alone could not elicit significant tumor regressions whereas chemotherapy following DC vaccination significantly improved the mean survival of patients (p=0.04). Although most of our patients did not show any objective clinical response, one of the patients in arm III (patient 3) with a prominent lung metastasis, showed an excellent response to cisplatin chemotherapy given nearly a year after the third DC vaccine dose.…”
Section: Discussionmentioning
confidence: 99%